Introduction to spectroscopy : A guide for students of organic chemistry - Pavia, Donald L.; Lampman, Gary M.; Kriz, George S. (Thomson Learning, 2001)
Covering important spectroscopic techniques used in the study of organic chemistry, this third edition is suitable to be used as the main text in a spectroscopy course, or as a supplement in a second year organic chemistry course. The text covers high resolution 300-MHz NMR spectra which replaces the older 60-MHz spectra. There is a survey section on 1H-NMR which provides a qualitative treatment of spectra by functional group, as well as a discussion on cross polarization in the 13C-NMR spectra and a "How to Solve Mass Spectrometry Problems" section.
Appendix 47p.
Keywords: Spectroscopy; Organic chemistry